THE EFFECT OF USING BEHAVIORISTIC THEORY ON STUDENTS’ SPEAKING SKILL OF RECOUNT TEXT - Gusparia Gusparia (Ensiklopedia of Journal, 2020)
The aim of this study is to find out the effectiveness of applying Behavioristic Theory on students’ speaking skill of recount text. The research design was experimental by giving pre-test and post-test to the class. It involved 25 participants of SMP N 3 Sungai Lala. The research question was posted in this study in order to find out the significant effect of applying behavioristic theory on students’ speaking skill of recount text. Pretest and posttest were administered in this study and sample t-test was used to analyze the data. The finding shows that there was no significant effect of behavioristic theory on students’ speaking skill. The mean level is 37,33 (for the experimental class) become 49,96 (for the control class). The finding of t-0 is -1.947; while the level of significance of 5% is 2.02 and the level of significant 1% is 2.64. It can be stated that 2.02>-1.947